Preparation method of hydrophobic fabric, hydrophobic fabric and application thereof

By reacting alkali lignin with metal ions to increase the roughness of the fabric surface, hydrophobic fabric is prepared, which solves the problem of environmental pollution in oil leakage, realizes oil-water separation, and increases the added value of alkali lignin.

CN116356567BActive Publication Date: 2024-12-24QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310433100.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-21
Publication Date
2024-12-24
Estimated Expiration
2043-04-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the environmental pollution problems caused by oil leakage, and there is a lack of low-cost, stable and reusable materials for oil/water separation.

Method used

By using hydroxyl groups, carboxyl groups, methoxy groups and other groups in alkali lignin to react with metal ions, hydrogen bonds are formed to connect with hydroxyl groups on the fabric, increasing the roughness of the fabric surface, and hydrophobic fabrics are prepared to achieve oil-water separation.

Benefits of technology

The prepared hydrophobic fabric has good oil-water separation performance, can effectively solve the environmental pollution problems caused by oil leakage, and provides a high-value utilization method of alkali lignin, and does not use harmful substances such as fluorine-containing substances and long-chain silanes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116356567B_ABST
    Figure CN116356567B_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a hydrophobic fabric, a hydrophobic fabric and an application thereof in oil-water separation, and belongs to a modification technology of a hydrophobic coating. The invention utilizes hydroxyl, carboxyl, methoxyl and other groups of alkali lignin to react with metal ions, and then forms hydrogen bonds with hydroxyl groups on the fabric to increase the roughness of the fabric surface, and obtains a hydrophobic fabric through surface modification, which is beneficial to providing a utilization method of alkali lignin. At the same time, the modified hydrophobic fabric has oil-water separation performance, can solve the environmental pollution problem caused by oil leakage to a certain extent, and has very important significance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a modification technology of a hydrophobic coating, and in particular to a preparation method of a hydrophobic fabric, the hydrophobic fabric prepared by the preparation method, and the application of the hydrophobic fabric in oil-water separation, wherein the fabric is preferably waste fabric. Background Art

[0002] In recent years, frequent oil spills and emissions of industrial organic pollutants have caused long-term damage to the ecological environment and human safety. The development of low-cost, stable and reusable materials for efficient oil / water separation remains a challenge. Since ancient times, the lotus leaf has been widely praised for its "coming out of the mud without being stained, washing in the water without being evil". Researchers have found that the lotus leaf has a rough microscopic morphology and hydrophobic epidermal wax on its surface, which gives the lotus leaf a unique wettability. Studies have found that the preparation of hydrophobic surfaces mainly starts from constructing a rough surface structure and reducing surface energy, which can generally be measured by the water contact angle (WCA). WCA>90° is hydrophobic.

[0003] Lignin is a natural polymer with a phenolic structure. It is widely found in woody plants, herbaceous plants, and vascular plants. It is the second largest natural polymer material in nature after cellulose in terms of quantity. It is environmentally friendly, pollution-free, and renewable. Lignin undergoes a certain alkaline hydrolysis in an alkaline environment, which increases its solubility and is extracted. After precipitation and separation, the resulting lignin is called alkali lignin. Alkali lignin contains functional groups such as hydroxyl, carboxyl, carbonyl, and methoxy. The presence of these functional groups makes it possible to modify lignin. Summary of the invention

[0004] In view of this, in order to achieve high-value utilization of alkali lignin and application of hydrophobic fabrics in oil-water separation, on the one hand, the present invention provides a method for preparing a hydrophobic fabric, which utilizes hydroxyl, carboxyl, methoxy and other groups of alkali lignin to react with metal ions, and then forms hydrogen bonds with hydroxyl groups on the fabric to increase the roughness of the fabric surface, and the surface is modified to obtain a hydrophobic fabric, which is beneficial to providing a utilization method for alkali lignin. At the same time, the modified hydrophobic fabric has oil-water separation performance, which can solve the environmental pollution problem caused by oil leakage to a certain extent, and is of great significance.

[0005] Without achieving the above purpose, the present invention provides the following technical solutions:

[0006] A method for preparing a hydrophobic fabric comprises the following steps: using groups contained in alkali lignin to react with metal ions, and then forming hydrogen bonds with hydroxyl groups on the fabric to increase the roughness of the fabric surface, and obtaining the hydrophobic fabric through surface modification.

[0007] Preferably, the groups include hydroxyl, carboxyl and methoxy.

[0008] Preferably, the method specifically comprises the following steps:

[0009] 1) uniformly mixing the alkali lignin aqueous solution and the metal ion aqueous solution to obtain a co-solvent system of the two;

[0010] 2) placing the fabric in the eutectic system in step 1), and sequentially immersing, taking out, and drying the fabric to obtain a hydrophobic fabric;

[0011] The fabric is preferably a pretreated fabric, and the pretreatment steps are as follows:

[0012] The fabric is washed with deionized water, ethanol, and deionized water in sequence, and then dried.

[0013] Preferably, the metal ion is Fe 2+ and Fe 3+ One of them.

[0014] Preferably, Fe 2+ From ferrous sulfate heptahydrate, Fe 3+ From ferric chloride.

[0015] Preferably, the mass concentration of the alkali lignin is 2 g / L; the mass concentrations of the ferrous sulfate heptahydrate and the ferric chloride solution are both 3 g / L.

[0016] Preferably, in step 2), the immersion temperature is 50° C., the immersion time is 24 hours, and the fabric is turned over every 4 hours;

[0017] In step 2), the drying temperature is 50°C.

[0018] Preferably, the fabric is one of 100% pure cotton, polyester-cotton a and polyester-cotton b;

[0019] The polyester-cotton a is 35% cotton + 65% polyester fiber, and the polyester-cotton b is 20% cotton + 80% polyester fiber.

[0020] In another aspect, the present invention provides a hydrophobic fabric prepared by the above-mentioned method for preparing the hydrophobic fabric.

[0021] In another aspect, the present invention also provides use of the hydrophobic fabric in oil-water separation.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1) The preparation method of the hydrophobic fabric provided by the present invention utilizes the hydroxyl, carboxyl, methoxyl and other groups of alkali lignin to react with metal ions, and then forms hydrogen bonds with the hydroxyl groups on the fabric to increase the roughness of the fabric surface, and the surface is modified to obtain the hydrophobic fabric, which is beneficial to providing a utilization method of alkali lignin. At the same time, the modified hydrophobic fabric has oil-water separation performance, which can solve the environmental pollution problem caused by oil leakage to a certain extent, and is of great significance.

[0024] 2) The present invention uses a simple method to react alkali lignin with metal ions to obtain an environmentally friendly hydrophobic coating that is applicable to a variety of substrates, and uses the coating to modify the surface of different waste fabrics to obtain durable hydrophobic fabrics, achieving self-cleaning and oil-water separation of the fabrics, and the present invention does not use any fluorine-containing substances, long-chain silanes, and organic solutions. At the same time, it provides a theoretical and practical basis for improving the added value of alkali lignin. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 In Example 1, pure cotton is used as the substrate, and alkali lignin is respectively mixed with FeⅡ (Fe 2+ )、FeⅢ(Fe 3+ )、CuⅡ(Cu 2 + ) Water contact angle of hydrophobic fabrics prepared by ion reaction;

[0026] Figure 2 In Example 2, polyester-cotton a is used as the base, alkali lignin and FeⅡ (Fe 2+ ) Water contact angle of hydrophobic fabrics prepared by ion reaction;

[0027] Figure 3 Based on polyester-cotton b, alkali lignin and FeⅢ (Fe 3+ ) Water contact angle of hydrophobic fabrics prepared by ion reaction;

[0028] Figure 4 It is a friction experiment device;

[0029] Figure 5 is the relationship between the friction times and water contact angle of AL / FeⅢ@cotton fabric in Example 1;

[0030] Figure 6 For oil-water separation experiments;

[0031] Figure 7 is the oil-water separation efficiency of AL / FeⅢ@polyester-cotton b in Example 2;

[0032] in, Figure 1-3 The original refers to pure cotton fabric. DETAILED DESCRIPTION

[0033] The invention provides a method for preparing a hydrophobic fabric, which utilizes groups contained in alkali lignin to react with metal ions and then form hydrogen bonds with hydroxyl groups on the fabric to increase the roughness of the fabric surface and obtain the hydrophobic fabric through surface modification.

[0034] In the present invention, the fabric is preferably waste fabric.

[0035] Alkali lignin contains functional groups such as hydroxyl, carboxyl, carbonyl and methoxyl groups. The presence of these functional groups provides the possibility for the modification of lignin. In the present invention, the groups include hydroxyl, carboxyl and methoxyl groups.

[0036] In the present invention, the following steps are specifically included:

[0037] 1) uniformly mixing the alkali lignin aqueous solution and the metal ion aqueous solution to obtain a co-solvent system of the two;

[0038] 2) placing the fabric in the eutectic system in step 1), and sequentially immersing, taking out, and drying the fabric to obtain a hydrophobic fabric;

[0039] The fabric is preferably a pretreated fabric, and the pretreatment steps are as follows:

[0040] The fabric is washed with deionized water, ethanol, and deionized water in sequence, and then dried.

[0041] In the present invention, the metal ion is Fe 2+ and Fe 3+ At least one of the following, Cu can also be selected 2+ .

[0042] In the present invention, Fe 2+ From ferrous sulfate heptahydrate, Fe 3+ From ferric chloride, Cu 2+ From copper sulfate.

[0043] In the present invention, the mass concentration of the alkali lignin is 2 g / L; the mass concentrations of the ferrous sulfate heptahydrate and the ferric chloride aqueous solution are both 3 g / L. 2+ , then the mass concentration of copper sulfate aqueous solution is 3g / L.

[0044] In the present invention, in step 2), the immersion temperature is 50° C., the time is 24 hours, and the fabric is turned over every 4 hours;

[0045] In step 2), the drying temperature is 50°C.

[0046] In the present invention, the fabric is one of 100% pure cotton, polyester-cotton a and polyester-cotton b;

[0047] The polyester-cotton a is 35% cotton + 65% polyester fiber, and the polyester-cotton b is 20% cotton + 80% polyester fiber.

[0048] In another aspect, the present invention provides a hydrophobic fabric prepared by the above-mentioned method for preparing the hydrophobic fabric.

[0049] In another aspect, the present invention also provides use of the hydrophobic fabric in oil-water separation.

[0050] The technical solution of the present invention is described clearly and in detail below in conjunction with specific embodiments.

[0051] Example 1

[0052] (1) The pure cotton fabric was first washed with deionized water and rubbed for 2 minutes, then soaked with anhydrous ethanol, and then rinsed with deionized water to remove dust and other impurities on the surface of the fabric. After taking it out, it was dried at 50°C for use;

[0053] (2) Take 0.30g of alkali lignin and dissolve it in 100ml of deionized water to obtain an alkali lignin aqueous solution; take 0.45g of ferrous sulfate heptahydrate and ferric chloride and copper sulfate and dissolve them in 50ml of deionized water to obtain FeⅡ(Fe 2+ ) aqueous solution, FeⅢ(Fe 3+ ) aqueous solution and CuⅡ(Cu 2+ ) aqueous solution. Then the alkali lignin aqueous solution is uniformly mixed with the above metal ion solution, and the volume is fixed to obtain a co-solvent system of the two;

[0054] (3) The pure cotton fabrics pretreated in (1) were placed in the alkaline lignin aqueous solution prepared in (2) and FeⅡ(Fe 2+ ) aqueous solution, FeⅢ(Fe 3+ ) aqueous solution and CuⅡ(Cu 2+ ) aqueous solution, immersed at 50°C for 24h, and turned over the fabric every 4h to ensure uniform deposition, and then taken out;

[0055] (4) The fabric treated in step (3) was placed in a constant temperature oven and dried at 50°C for 4 h to obtain AL / FeⅡ@cotton fabric, AL / FeⅢ@cotton fabric and AL / CuⅡ@cotton fabric, respectively.

[0056] (5) Use an optical contact angle meter (OCA50) to test the water contact angle (WCA) of the modified fabric surface. Control the syringe to drop 8 μL of water on the surface of the test sample, take a photo of the droplet, and measure its corresponding contact angle. The average value of five tests is taken as the test result. The results are as follows: Figure 1 shown.

[0057] Depend on Figure 1It can be seen that pure cotton fabric after being treated with alkali lignin and FeⅡ(Fe 2+ )、FeⅢ(Fe 3+ )、CuⅡ(Cu 2+ ) and then the contact angle increased. The unmodified pure cotton fabric is super hydrophilic, with an initial contact angle of 75.6° and the water droplets are absorbed after 6s. The modified pure cotton fabrics are all hydrophobic, and the initial contact angle of AL / FeⅢ@cotton fabric can reach 131.9°. The water droplets stay for 30 minutes without being absorbed, and have good hydrophobic stability. AL / FeⅡ@cotton fabric also has a high contact angle and good hydrophobic stability. Therefore, AL / FeⅢ and AL / FeⅡ coatings have good hydrophobicity and stability and can be used for oil-water separation.

[0058] Example 2

[0059] (1) First, the polyester-cotton a and the polyester-cotton b are washed and rubbed with deionized water for 2 minutes, then soaked with anhydrous ethanol, and then rinsed with deionized water to remove dust and other impurities on the surface of the fabrics. After taking out, they are dried at 50° C. for use;

[0060] (2) Take 0.30g of alkali lignin and dissolve it in 100ml of deionized water to obtain an alkali lignin aqueous solution; take 0.45g of ferrous sulfate heptahydrate and ferric chloride and dissolve them in 50ml of deionized water to obtain FeⅡ(Fe 2+ ) aqueous solution and FeⅢ(Fe 3+ ) aqueous solution. Then the alkali lignin aqueous solution was mixed with FeⅡ(Fe 2+ ) aqueous solution and FeⅢ(Fe 3+ ) aqueous solutions are uniformly mixed and fixed to volume to obtain a co-solvent system of the two;

[0061] (3) The polyester-cotton a and polyester-cotton b pretreated in (1) are placed in the alkaline lignin aqueous solution prepared in (2) and mixed with FeⅡ(Fe 2+ ) aqueous solution and FeⅢ(Fe 3+ ) aqueous solution, immersed in a co-solvent system formed by 50°C for 24h, and turning the fabric over every 4h to ensure uniform deposition, and then taking it out.

[0062] (4) The fabric treated in step (3) was placed in a constant temperature oven and dried at 50°C for 4 h to obtain AL / FeⅢ@polyester-cotton a, AL / FeⅢ@polyester-cotton b, AL / FeⅡ@polyester-cotton b and AL / FeⅡ@polyester-cotton a, respectively.

[0063] The water contact angle (WCA) of the modified fabric surface was tested using an optical contact angle meter (OCA50). The syringe was controlled to drop 8 μL of water on the surface of the test sample, and the droplet was photographed and its corresponding contact angle was measured. The average value of five tests was taken as the test result. The results are shown in Figure 2. Figure 2-3 shown.

[0064] Depend on Figure 2-3 It can be seen that alkali lignin / FeⅡ and alkali lignin / FeⅢ hydrophobic coatings can improve the hydrophobicity of different substrates. After the surface of cotton fabric, polyester-cotton a and polyester-cotton b was modified by alkali lignin / FeⅢ hydrophobic coating, the initial contact of cotton fabric, polyester-cotton a and polyester-cotton b increased compared with the unmodified fabric, and the contact angle of AL / FeⅢ@polyester-cotton a can reach 126.6°. Moreover, the water droplets stayed on the three fabrics for more than 30 minutes, with good hydrophobic stability, and oil-water separation can be performed. Therefore, the hydrophobic coating can be used to improve the hydrophobicity of different waste fabrics.

[0065] In the above-mentioned embodiment 1-2 of the present invention, AL is alkali lignin.

[0066] Friction resistance test

[0067] (1) Place the AL / FeⅢ@cotton fabric and AL / FeⅡ@cotton fabric prepared in Example 1 on a smooth plane.

[0068] (2) Place a 100-gram weight on the AL / FeⅢ@cotton fabric and AL / FeⅡ@cotton fabric, and use the weight to pull the cotton fabric on the table to make it rub repeatedly.

[0069] (3) Each slide of 40 cm is set as one cycle, and the static contact angle between the cotton fabric and water is measured after 0, 50, 100, 150, 200, 250, and 300 cycles respectively. The stability of the fabric is judged based on the test results of the contact angle. Figure 3

[0070] (4) Use an optical contact angle meter (OCA50) to test the water contact angle (WCA) of the modified fabric surface. Control the syringe to drop 8 μL of water on the surface of the test sample, take a photo of the droplet, measure its corresponding contact angle, and take the average value of five tests as the test result. The results are shown in Figure 4-5 shown.

[0071] like Figure 4-5 The left side shows the friction resistance test process. A 100g weight is used to drive the modified fabric to rub 40cm on the table. Figure 5It can be seen that the contact angle of AL / FeⅢ@cotton fabric increases first and then decreases with the increase of friction times. Because the fabric fibers are broken at the beginning of friction, the fine fibers are exposed on the surface, the surface roughness is increased, and the contact angle value increases; further friction exposes the fine fibers and is worn away from the fabric, and the contact angle decreases. When rubbed 200 times, the maximum contact angle is 137.6°, and the contact angle is still 126° when rubbed 500 times. The contact angle of AL / FeⅡ@cotton fabric gradually decreases with the increase of friction times, but it is still 138.4° after rubbing 500 times. Therefore, the fabric has good friction resistance and still has good hydrophobicity after rubbing 500 times.

[0072] Oil-water separation experiment

[0073] like Figure 6-7 As shown, (1) Preparation of oil-water mixture: In the oil-water separation experiment, 30 ml of deionized water and 30 ml of oil dyed with Oil Red O were mixed in equal volumes. In this experiment, toluene, carbon tetrachloride, dichloromethane, chloroform, n-hexane, and petroleum ether were selected as experimental oils for hydrophobic fabrics.

[0074] (2) Oil-water separation: In order to remove chloroform, dichloromethane, and carbon tetrachloride, which have a density greater than that of water, gravity is used as the driving force to separate the oil and water. The oil-water mixture is poured onto the fabric for oil-water separation; in order to remove toluene, n-hexane, and petroleum ether, which have a density less than that of water, a peristaltic pump is used for oil-water separation.

[0075] (3) Calculate the separation efficiency. The calculation formula of the separation efficiency η is shown in (1). Repeat the above operation 30 times to test the reusability of the fabric.

[0076]

[0077] M0: water mass before separation;

[0078] M1: The mass of water after separation.

[0079] Modified AL / FeⅢ@cotton fabric and AL / FeⅡ@cotton fabric can be used for oil-water separation (such as Figure 6 As shown), heavy oil (chloroform, dichloromethane) and light oil (toluene, hexane) are dyed with oil red, and deionized water is dyed with blue dye. Figure 7 As shown in the figure, the red oil and blue deionized water are separated by peristaltic pump and gravity, and the oil-water separation efficiency of AL / FeⅢ@cotton fabric and AL / FeⅡ@cotton fabric is above 95%, and the separation efficiency of AL / FeⅢ@cotton fabric for n-hexane can reach 99%. Therefore, the hydrophobic light oil fabric obtained by this modification method can be used for oil-water separation.

[0080] The above are only preferred embodiments of the present invention; however, the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and improved concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a hydrophobic fabric, characterized in that: The groups contained in the alkali lignin react with metal ions and then form hydrogen bonds with the hydroxyl groups on the fabric to increase the roughness of the fabric surface, and the surface modification results in a hydrophobic fabric. The groups include hydroxyl, carboxyl and methoxy; The specific steps include: Step 1), uniformly mixing the alkali lignin aqueous solution and the metal ion aqueous solution to obtain a co-solvent system of the two; Step 2), placing the fabric in the eutectic system in step 1), and sequentially immersing, taking out, and drying to obtain a hydrophobic fabric; In step 2), the immersion temperature is 50° C., the time is 24 hours, and the fabric is turned over every 4 hours; In step 2), the drying temperature is 50°C; The fabric is a pretreated fabric, and the pretreatment steps are as follows: The fabric is washed with deionized water, ethanol, and deionized water in sequence, and dried; The metal ion is Fe 2+ and Fe 3+ One of; The fabric is 100% cotton.

2. The method for preparing a hydrophobic fabric according to claim 1, characterized in that: Fe 2+ From ferrous sulfate heptahydrate, Fe 3+ From ferric chloride.

3. The method for preparing a hydrophobic fabric according to claim 2, characterized in that: The mass concentration of the alkali lignin is 2 g / L; the mass concentrations of the ferrous sulfate heptahydrate and the ferric chloride solution are both 3 g / L.